af006020: IUSY congress - IUSY; Drijbooms, Dirk (1987)
"Affiche uitgegeven in 1987 door de International Union of Socialist Youth (IUSY) voor een congres. Afbeelding: foto van een rode vuist waarin een rode roos. Tekst: iusy international union of socialist youth. congreso congress. youth and crisis challenges to socialism. la juventud y la crisis un desafío al socialismo. XVII congreso iusy congress. 2.-4. octubre 1987 Bruselas. 2.-4. october 1987 Brussels. responsable editor: Dirk Drijbooms; IUSY - A-1070 Vienna, Neustiftgasse 3, Austria. FULL TEXT AVAILABLE AT AMSAB-ISH"